Cahiers du Sart Tilman - Ulrix-Closset, Marguerite; Lemoine, Willy; Christians, Charles; Grégoire, Henri (Liège: Université de Liège, 1963)
"Ce cahier a été mis au point et réalisé par Henri Grégoire Bibliotheek Camille Huysmans"